Rights and Obligations of Husband and Wife (Theological Normative and Sociological Approach) - Fauzi Rahmat Pamula; Sayehu (Jurnal Hukum Keluarga, 2024)
Marriage in Islam regulates the rights and obligations of husband and wife, which are important for the creation of harmony in the household. However, the implementation of these rights and obligations is often influenced by various social, cultural and economic factors, which can have both positive and negative impacts on the husband-wife relationship. This study aims to analyze the rights and obligations of husband and wife from the perspective of the Qur'an and hadith, and identify the social factors that influence their implementation in society. The main research questions are how religious teachings on the rights and obligations of husband and wife are translated into social practices, and what social impacts arise from their application in daily life. This study uses the Library Research method with a qualitative approach, analyzing the texts of the Qur'an, hadith, tafsir, as well as related literature, by connecting the theories of sociology of religion and social justice. The findings of this study indicate that a balanced and fair application of rights and obligations can strengthen the husband-wife relationship and create family harmony. However, an imbalance in the fulfillment of rights and obligations can lead to conflict, inequality and even domestic violence, affecting the overall quality of family life. Thus, this study emphasizes the importance of understanding the social and cultural context in the application of religious teachings to achieve a harmonious and just household.